MEASURING THE IMPACT OF FINANCIAL SOUNDNESS INDICATORS ON BANKS' OBLIGATIONS TO DEPOSITORS-A FIELD STUDY OF A GROUP OF PRIVATE COMMERCIAL BANKS FOR THE YEARS 2020 TO 2023 - Salam Idan Marzouk; Inas Hussein Alwan (Scholar Express Journals, 2025)
Financial safety in commercial banks is one of the main pillars in their business, as it reflects the greatest concern of depositors and lenders in Commercial Bank before dealing with it, as well as the bank's management to ensure that the bank fulfills its obligations towards its depositors and invests these deposits in safe investment activities while ensuring profits. From this picture, the researcher's idea began by explaining the concept of financial safety in commercial banks, its importance, its indicators approved by the Central Bank of Iraq, and the extent of their impact and evaluation of the bank's commitment to its depositors. The researcher used financial soundness indicators (Capital Adequacy Index (CAR), Liquidity Index (LIQ) and Non-Performing Loans (NPL) ) as an independent variable, as these indicators are the most influential in the bank's obligations towards its depositors, while the dependent variable was used by the researcher as an index (the ratio of total deposits to total liabilities). By adopting two banks, (Commercial Economy Bank and Middle East Investment Bank) as an intentional sample for research and a time series that spanned four years (2020-2023). The researcher starts from the hypothesis that there is a strong and significant correlation and effect relationship between the independent variable and the dependent variable, and tries to prove it using financial analysis as well as statistical analysis. The researcher reached a set of conclusions, the most important of which are: the non-compliance of commercial banks with the ratios of financial soundness set by the Central Bank, whether by neglecting the increase or decrease, as well as the fact that the Bank of Economy is exposed to a very high percentage of non-performing credit facilities, and that the non-performing loans index has no significant impact on the bank's obligations towards its depositors in most of the banks in the research sample. There were also a set of recommendations, the most important of which The need to adhere to the financial ratios set by the Central Bank, as well as the need to formulate efficient credit policies to avoid the default of the credit granted by commercial banks.
Keywords: Financial Soundness Indicators; Bank Liabilities